[Supplemental material] Activated carbon from pumpkin seeds: Production by simultaneous carbonization activation for occupational respiratory protection - Silva, Walquíria Joseane; Andrade Neto, Nivaldo Freire; Paskocimas, Carlos Alberto; Ruiz, Juan Alberto Chaves; Carvalho, Fabíola Correa; Longo, Elson; da Motta, Fabiana Villela; Delmonte, Maurício Roberto Bomio (Eclética Química, 2022)
Activated carbon materials are derived from carbonaceous sources and used as a technological element for various industrial purposes. These materials are present in most filters (cartridges) in personal respiratory protective equipment. Due to this context and to enhance sustainability concepts and human health in the production of materials, this study aimed to produce activated carbon from an abundant agricultural waste in the northeast Brazil through a route that not only favors its simultaneous carbonization and activation but also its thermal neutralization. The precursor biomass was characterized by particle size analysis, a standard testing method for moisture and ash content which were characterized by FRX, CHN, and thermal analysis. The produced activated carbon was characterized by potential of hydrogen (pH), XRD, BET, SEM, TPD by ammonia and UV-Vis analysis. The activated carbons showed yields between 73 and 78%. The morphology varied in function of the biomass interaction with the type and concentration of acid used. The produced samples showed adsorption capacity and selectivity to ammonia gas.